Preparation and characterization of titanium dioxide thin films by SILAR method - Pathan, HM; Min, SK; Desai, JD; Jung, KD; Joo, OS (ELSEVIER SCIENCE SA, 2006)
Successive ionic layer adsorption and reaction (SILAR) is a process for depositing uniform, crystalline and conformal thin films by alternating exposures to cations and anions. SILAR has been successfully demonstrated for many metal oxides, but not for titanium dioxide (TiO2). Here we demonstrate process for deposition of TiO2 thin films using SILAR method. Titanium tri-chloride and ammonium hydroxide were used as cationic and anionic sources, respectively. Their surface reactions were found to be complementary and self-limiting, thus providing compact, uniform films with control over thickness of the film. The preparative conditions were optimized to get good-quality TiO2 thin films. The films have been characterized for structural, morphological, compositional, optical and photo-response properties. Growth process, reaction mechanism and annealing effect are also discussed. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: DEPOSITION; OXIDE; ELECTRODEPOSITION; PHOTOCATALYST; ANATASE